Why did shareholder liability disappear? - David A. Bogle; Gareth Campbell; Christopher Coyle; John D. Turner (Queen's University Centre for Economic History (QUCEH), 2022)
Why did shareholder liability disappear? We address this question by looking at its use by British insurance companies from 1830 until its complete disappearance by 1975. We explore three explanations for its demise: (1) regulation and government-provided policyholder protection meant that it was no longer required; (2) it had become de facto limited; and (3) shareholders saw an opportunity to expunge something they disliked when insurance companies grew in size. Using hand-collected archival data, our findings suggest investors attached a risk premium to shareholder liability, and it was phased out after a merger movement increased the size of insurance companies which meant that they were better able to pool risks.
Keywords: G11; G22; N20; N40; 330; Insurance; regulation; shareholder liability; United Kingdom